Second language anxiety among universiti utara Malaysia students. - Abd Aziz, Noor Hashima; Wan Chek, Noor Allam; Abdul Ghani, Ahmad Mahreez; Jupri, Rohaiza; Yusoff, Nooraini
The purpose of this research is to investigate the level of language anxiety among Universiti Utara Malaysia students taking Public Speaking and Business Report Writing courses. This research also investigated the differences between gender, ethnicity, first language and four anxiety constructs, namely communication apprehension, fear of negative evaluation, test anxiety and anxiety in the English classroom. The instrument used for the study was adapted from Horwitz’s the Foreign Language Classroom Anxiety Scale (FCLAS). The questionnaire was distributed to 418 students using a Bahasa Melayu version. The findings from this study has identified that there are different levels of anxiety which are high, neutral and low among the respondents. Further analysis has also found significant differences between ethnicity and first language towards fear of negative evaluation and anxiety in the English classroom. The other two constructs (communication apprehension and test anxiety) were found to be not significant. The results, pedagogical implications and recommendations for future research are also discussed. Keywords: Language anxiety, Foreign Language Classroom Anxiety Scale (FLCAS), communication apprehension, fear of negative evaluation, test anxiety and anxiety in the English classroom